Intellectual Property Rights and Food Security - Blakeney, Michael (CABI, 2014)
At the time of the first World Food Summit in 1996 it was estimated that more than 800 million people did not have enough food to meet their basic nutritional needs. The steep rise in global food prices has exacerbated the situation, causing the 2008 G8 Hokkaido Toyako Summit to issue a Statement on Food Security which expressed concern that global food security was under a severe threat. The root cause of food insecurity is poverty. Trade liberalization is part of the long-term solution, as are improvements in agricultural productivity. This book examines the contribution which intellectual property rights can make in the struggle for food security in developing countries. Chapter 1 locates intellectual property rights within the armoury of food security policies. Chapter 2 deals with definitional issues and examines the role of intellectual property rights in incentivizing agricultural research and development. Chapter 3 examines the international landscape of intellectual property and the approaches taken to the relationship between intellectual property rights, agricultural biotechnology, access to biological resources, food security and globalization which are taken by the WTO, FAO, CBD and WIPO among the various international and development agencies. Plant variety rights (PVRs) are a specially created form of intellectual property right originally minted to encourage agricultural innovation and Chapter 4 examines the effectiveness of PVRs in a food security context. Agricultural innovation is in part dependent upon access of researchers to the genetic resources of the biodiverse countries of the South. Chapter 5 considers the attempts to construct an international regime to secure this access. The important role of traditional farmers in preserving landraces and cultivars from which improvements can be derived has generated for a call for the recognition of farmers’ rights, and this is examined in Chapter 6 together with agitation for the protection of the traditional knowledge which often informs access to the useful genetic resources.